The Smell of the Greasepaint, the Roar of the Crowd …: Disruptive Audiences - Butcher, Ian (Peripeti, 2025)
Abstract Theatre audiences have become more vocal, rowdy and violent to the point of disrupting, interrupting or even stopping productions. Some new theatregoers do not know, or disregard, the accepted theatre etiquette of remaining silent in respect for the actors and fellow audience members during the performance. In this age of (mis)use of social media, theatres have to adapt their offerings on stage and front-of-house in order to attract and educate these new audiences who view the world somewhat differently from their older generational counterparts. Abstract Teatre oplever i dag, hvordan publikum er blevet mere højlydte og urolige og endda afbryder og ligefrem stopper en forestilling. Visse nye publikummer har ikke hørt om, eller ignorerer acceptabel teater etikette såsom at forholde sig rolig af respekt for skuespillerne og resten af publikum under forestillingen. I vore dage hvor alle (mis)bruger sociale medier, er teatrene ofte nødsaget til at ændre deres tilbud både på scenen og foran scenen for at kunne tiltrække og uddanne disse grupper af nye teatergængere, som ser verden i et noget andet lys end den ældre generation.